2015
DOI: 10.1590/0102-37722015032099339348
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento da Compreensão Emocional

Abstract: RESUMO -A compreensão emocional é uma componente-chave da competência emocional, que se tem vindo a constatar ser importante para um melhor entendimento do desenvolvimento infantil. Este artigo faz uma revisão teórica desse construto, situando-o nos estudos sobre inteligência emocional e clarificando a sua definição. Apresentam-se, igualmente, os diferentes instrumentos que existem para a sua avaliação assim como os estudos que trazem evidências sobre o seu desenvolvimento. Concluiu-se que está demonstrada a e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 25 publications
1
8
0
13
Order By: Relevance
“…There is evidence that age is a significant predictor of emotion understanding, but not of social competence. In this study, the general scoring in emotion understanding increases regularly with age, as previously found in other studies carried out with TEC ( Farina et al, 2007 ; Albanese et al, 2010 ; Santos, 2012 ; Silva, 2012 ; Franco and Santos, 2015 ). On the other hand, despite the fact that some studies indicate a connection between age and the development of social competences ( Cecconello and Koller, 2000 ; Major, 2011 ), in this study these relationships were not found.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There is evidence that age is a significant predictor of emotion understanding, but not of social competence. In this study, the general scoring in emotion understanding increases regularly with age, as previously found in other studies carried out with TEC ( Farina et al, 2007 ; Albanese et al, 2010 ; Santos, 2012 ; Silva, 2012 ; Franco and Santos, 2015 ). On the other hand, despite the fact that some studies indicate a connection between age and the development of social competences ( Cecconello and Koller, 2000 ; Major, 2011 ), in this study these relationships were not found.…”
Section: Discussionsupporting
confidence: 88%
“…The concept of emotional competence emerges associated to different processes and abilities, having present the multitude of concepts that are studied as analogs to this one, such as emotional knowledge, emotional comprehension, emotional intelligence and emotional regulation ( Bridges et al, 2004 ; Garner, 2010 ; Franco and Santos, 2015 ; McCormick et al, 2015 ; Roazzi et al, 2015 ; Djambazova-Popordanoska, 2016 ), and also taking into account the number of measuring instruments used in its assessment, such as observation, self-assessment or hetero-assessment ( Djambazova-Popordanoska, 2016 ). On the other hand, the most studied abilities can be grouped into three components: emotional expression, emotional regulation and emotion understanding ( Denham et al, 2003 ; Denham, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A compreensão emocional (CE) é um conceito desenvolvimental, que tem sido estudado junto com o conhecimento emocional, a inteligência emocional ou regulação emocional, ora como sendo sinónimo de uns, ora como sendo uma parte de outros, ora como tendo uma individualidade própria (Djambazova-Popordanoska, 2016;Franco & Santos, 2015;. Em 2004, Pons, Harris, e Rosnay propuseram um paradigma de pesquisa que tem possibilitado investigar de forma mais precisa a CE em crianças considerando, simultaneamente, nove componentes que, em função do nível de desenvolvimento, podem ser agrupadas em três fases: uma fase externa (3-6 anos) que envolve a possibilidade de identificar expressões faciais que indicam uma emoção, causadas por fatores externos e a capacidade de recordar uma lembrança passada que possa causar uma emoção; uma fase mental (5-9 anos) que compreende a capacidade de compreender que as emoções são resultantes de crenças e desejos individuais, envolvendo a diferenciação entre estados reais e aparentes, o que é baseado na compreensão de representações mentais; e uma fase reflexiva (8-12 anos) que inclui a possibilidade de identificar que uma pessoa pode sentir mais do que uma emoção, a compreensão das emoções morais (como culpa) e o controle mental das emoções (Pons Harris, & Rosnay, 2004).…”
unclassified
“…Transformações de 3 para 4 anos, apesar de controversas, são reportadas pela literatura (Hughes, 2011;Wellman, 2014) (Harris, 1996). Além disso, a criança, ao lidar primeiramente com representações emocionais distintas, torna-se hábil para equacionar representação de crenças conflitantes como para ajustar o seu comportamento em função dos parceiros e do contexto específico (Franco & Santos, 2015;Santana & Roazzi, 2006;Wellman, 2014).…”
Section: Desempenho Da Terceira Criança Nounclassified